Hydrodeoxygenation of aliphatic acid over NiFe intermetallic compounds: Insights into the mechanism via model compound study. (1st December 2021) - Han, Depeng; Yin, Wang; Luo, Dan; He, Han; Wang, Shengping; Xia, Shuqian
Graphical abstract: Formation of Ni-Fe intermetallic compound facilitated the remove of the "first oxygen" in fatty acid because of the strong spin polarization and increased charge density around Ni site. Highlights: Ni7.5 Fe2.5 /SiO2 intermetallic compound catalyst promotes the rate-determining step C11 H23 COOH → C11 H23 CHO in the hydrodeoxygenation of lauric acid. Improved electronic density around Ni site promotes the adsorption and dissociation of H2 with an appropriate introduction of Fe. Strong spin polarization of Fe lead to the stronger interaction between spin down d orbital of bimetallic site and the outermost orbital of = O in aliphatic acid. Reduced Ni-Fe bimetallic sites rather than oxidized ones can promote the selectivity of alkanes. Abstract: Hydrodeoxygenation (HDO) is a promising way to produce the second generation bio-diesel from aliphatic acid based biomass. Compared with the monometallic Ni/SiO2, appropriate introduction of Fe results in the complete conversion of lauric acid and nearly 100% yield of alkane as well as satisfactory stability on conversion. Further study on mechanism shows that the NiFe intermetallic compounds (IMC) catalyst promotes the ratedetermining step, i.e., C11 H23 COOH → C11 H23 CHO, which is attributed to the synergistic effect of Ni-Fe bimetallic sites according to the characterization and calculation. For one thing, strong spin polarization enhances the interaction between Fe sites and aliphatic acid, and the subsequent dissociation of C-OH bond indicated by the DOS and transition state analysis. For another, dissociation of H2 on Ni site is promoted because of the higher charge density around Ni in the IMC according to the in-suit FTIR and Bader analysis. However, with the repeated use of the catalyst, the selectivity to alkane decreased gradually, which is ascribed to the oxidation of metal Ni-Fe bimetallic sites. This demonstrates that the reduced Ni-Fe bimetallic sites rather than the oxidized ones are the active phases in the HDO of aliphatic acid to produce alkanes with the NiFe IMC.